PENERAPAN MODEL PEMBELAJARAN TEMATIK INTEGRATIF DI SD (STUDI PADA KURIKULUM MERDEKA) - Atma Lutfia Rizki (Jurnal Salome : Multidisipliner Keilmuan, 2026)
Integrative thematic learning is a holistic educational approach that connects various disciplines within a unified theme relevant to students’ real-life experiences. This study aims to describe the implementation of the integrative thematic learning model in elementary schools within the context of the Merdeka Curriculum, as well as to identify the supporting factors and challenges faced by teachers in its implementation. This research employed a qualitative approach using a field study method. Data were collected through observation, interviews, and documentation, and were analyzed descriptively. The findings indicate that the implementation of the integrative thematic learning model has been carried out quite effectively, as reflected in lesson planning aligned with learning outcomes, the use of varied instructional media, and active student engagement in the learning process. The implementation of the integrative thematic learning model within the Merdeka Curriculum can serve as an effective strategy to improve the quality of learning in elementary schools, provided that it is supported by careful planning, teacher creativity, and institutional support.